Pesquisa de criadouros naturais, impacto de medidas de controle e dinâmica de flebotomíneos no sul do Brasil - Castro, Kárin Rosi Reinhold de (2014)
We report the results of an investigation on natural breeding sites, and the results of control measures introduced to reduce density of sand flies in domiciles and subsequent monitoring of the effects of these measures on the population of these insects. The research was conducted in the Recanto Marista, Doutor Camargo municipality, Paraná state, Brazil. Sand flies were collected with Falcão traps for evaluation of control measures, from July 2006 to November 2007. The most frequent species were Nyssomyia neivai and Nyssomyia whitmani. A total of 268,382 (93.4%) sand flies were collected in ecotypes constructed with the aim of attract sand flies, and 19,091 (6.6%) sand flies were collected in the ecotypes consisting of residences and other buildings. For research on breeding sites of sand flies was used Alencar emergence traps, experimental traps, and soil samples incubated in BOD incubator, from May 2010 to August 2012. Eight sandflies were collected with Alencar emergence traps, one specimen with experimental trap and 21 in soil samples. The collected species were Brumptomyia brumpti, Micropygomyia ferreirana, Migonemyia bursiformis, Migonemyia migonei, Ny. neivai, Ny. whitmani, and Pintomyia pessoai. Human actions determine the growth or reduction of the sand fly population in human-occupied space. Understanding the dynamics of sand flies in this environment can substantially contribute to the prevention of cutaneous leishmaniasis. Natural breeding sites of sand flies were located in the Recanto Marista, especially between tree roots, however the amount of adults that emerged in the traps and soil samples was small depite the high density of sand flies that has been recorded in the Recanto Marista.